TRENDS IN THE DEVELOPMENT OF SPORTS AND PHYSICAL EDUCATION IN THEREPUBLIC OF UZBEKISTAN - Bahromjon Allayarovich Kazakov (Proximus Journal Publishing, 2024)
This article discusses the development of sports and physical culture in Uzbekistan, consistent work to improve the material and technical base necessary for the formation of future champions.
Keywords: Sport; physical culture; talented athletes; three-stage system